The checklist manifesto : how to get things right - Gawande, Atul (Metropolitan Books, 2010)
Reveals the surprising power of the ordinary checklist now being used in medicine, aviation, the armed services, homeland security, investment banking, skyscraper construction, and businesses of all kinds.